Makna Kebangkitan Yesus Dalam Kehidupan Para Murid: Tinjauan Terhadap Yohanes 21: 1 - 14 - Andreas Joswanto; Elisua Hulu (Sekolah Tinggi Teologi Sola Gratia Indonesia, 2023)
A very important aspect of the Christian faith is the work of Christ through His resurrection. This event became a basic concept in Christian doctrine. The meaning of Christ's resurrection does not only concern the futurist aspect, but also the presentist aspect in the lives of believers. The event after the resurrection is the appearance of Jesus himself, in the text of the Gospel of John 21 it is the third time Jesus appeared to his disciples. The study of the text of the Gospel of John 21: 1-14 uses descriptive research through library data sources with the aim of finding the meaning of resurrection in life. The meaning of Christ's resurrection in life or the presentist aspect is understood in the challenges of life, both in physical and spiritual aspects. Resurrection is an event that will be experienced by humans in the future and a resurrection that refers to Jesus Christ is a resurrection that happened in the past (historical) or has already happened. The meaning of Christ's resurrection in life, does not only talk about aspects of the past, present as well as the future. Anxiety and impatience always make a person who is quick to deal with human logical thinking. The Resurrection of Christ is not only talking about the futurist aspect, but also the presentist aspect. ABSTRAK BAHASA INDONESIA Aspek yang sangat penting dalam iman Kristen adalah karya Kristus melalui kebangkitan-Nya. Peristiwa ini menjadi konsep dasar dalam doktrin kekristenan. Makna kebangkitan Kristus tidak hanya menyangkut aspek futuris, juga aspek presentis dalam kehidupan orang percaya. Peristiwa setelah kebangkitan adalah penampakkan diri Yesus, dalam teks Injil Yohanes 21 merupakan ketiga kalinya Yesus menampakkan diri kepada murid-murid-Nya. Kajian terhadap teks Injil Yohanes 21: 1-14 menggunakan penelitian deskriptif melalui sumber data pustaka dengan tujuan menemukan makna kebangkitan dalam kehidupan para murid. Pemaknaan kebangkitan Kristus dalam kehidupan atau aspek presentis dipahami dalam tantangan kehidupan, baik dalam aspek jasmani maupun rohani. Kebangkitan merupakan peristiwa yang akan dialami oleh manusia di masa mendatang (bersifat future) dan kebangkitan yang merujuk pada Yesus Kristus adalah kebangkitan yang terjadi masa lampau (bersifat historis) atau sudah terjadi. Makna kebangkitan Kristus dalam kehidupan, tidak hanya berbicara aspek masa lalu (past), masa kini (present) juga masa yang akan datang (future). Kekuatiran dan ketidaksabaran selalu menjadikan pribadi yang cepat menghadapi dengan cara berpikir logika manusia. Kebangkitan Kristus tidak hanya berbicara aspek futuris, namun juga aspek presentis.